Monitoring of the electron beam position in industrial linacs - Boriskin, V.N.; Savchenko, A.N.; Tatanov, V.I.; Uvarov, V.L.; Shevchenko, V.A. (Вопросы атомной науки и техники, 2001)
Recently the technological linear electron accelerators with the energy up to 10 and 25 MeV and the pulse current up to 1A have been developed and put into operation in the "Accelerator" R&D Production Establishment of the National Science Center, Kharkov Institute of Physics and Technology [1]. The zone of the technological object irradiation by the accelerated electrons is created by the magnetic scanning system. Wide-aperture (50x200 and 50x300 mm) magneto-induction position monitors have been designed to control the electron beam position. Signals from the monitor are used in the accelerator control system.